The interplay between relationships, technologies and organizational structures in enhancing supply chain resilience: empirical evidence from a Delphi study - Küffner, Christoph; Kopyto, Matthias; Wohlleber, Annika; Hartmann, Evi (International Journal of Physical Distribution & Logistics Management, 2022)
Purpose COVID-19 has highlighted the need to reflect on how firms should improve their supply chains (SCs) to enhance agility and robustness. Recent studies focus more on the short-term rather than on the long-term developments and lack insights regarding the enhancement of supply chain resilience (SCRES) based on the interplay between multiple levers. Therefore, using a long-term perspective, this research evaluates the interaction between three SCRES levers – relationships, technologies and organizational structures – to improve SCRES. Design/methodology/approach Based on an extensive literature review, multiple interviews and workshops, 13 future projections were developed. These projections were assessed using a two-round Delphi study that included 83 international experts from industry, academia and politics/associations to determine the probability of occurrence by 2035, their impact on SCRES and their desirability. Findings This study provides empirical evidence that the long-term enhancement of SCRES is achieved through the interplay of multiple levers rather than unilateral optimization. The study suggests that, by 2035, collaboration between SC partners will be a key factor for SCRES enhancement. Additionally, SC stakeholders should be aware that failing to invest in digital technologies will negatively impact the agility and robustness of future SCs. Furthermore, humans are expected to continue to play a major role, given that relationship-oriented tasks are perceived to remain important. Originality/value This paper adds to current literature, describing how SCRES can be improved in the long term through the interplay of multiple levers and the combination of robust and agile elements. Considering the importance of ensuring resilient SCs, this paper provides valuable insights for academics and practitioner
Keywords: Supply chain resilience; Interplay; Relationships; Technologies; Organizational structures; Delphi study